Hematochezia in Young Patient Due to Crohn’s Disease - Anna Mira Lubis; Marcellus Simadibrata; Dadang Makmun; Ari F Syam (The Indonesian Society for Digestive Endoscopy, 2006)
Crohn’s disease encompasses a spectrum of clinical and pathological patterns, affecting the gastrointestinal (GI) tract with potential systemic and extraintestinal complications. The disease can affect any age group, but the onset is most common in the second and third decade. Lower GI bleeding is one of its clinical features. Surgical intervention is required in up to two-thirds of patients to treat intractable hemorrhage, perforation, obstruction or unresponsive fulminant disease. We reported a case of Crohn’s disease in young male who suffered from severe lower GI bleeding (hematochezia) as the clinical features. Lower GI endoscopy revealed ulceration at the distal ileum surrounded by fibrotic tissue as a source of bleeding and a tumor mass at mesocolon. Upper GI endoscopy was unremarkable. Histopathologyc examination concluded multiple ulceration with chronic ischemic condition, appropriate to Crohn’s disease. The patient underwent emergency surgical intervention (subtotal colectomy and ileustomy), and his condition was improved. Keywords: hematochezia, young male, Crohn’s disease, surgery